Shopping Life Style dan Stimulus Media Iklan Terhadap Ekpetasi Pelanggan (Studi Kasus Produk Fashion): Shopping Life Style dan Stimulus Media Iklan Terhadap Ekpetasi Pelanggan (Studi Kasus Produk Fashion) - Taat Kuspriyono (MANAJEMEN DEWANTARA, 2022)
As a woman, of course there is a desire to buy and try various desired products. This is not strange considering that as a woman, of course, you want to look elegant and beautiful. Before buying, of course, someone will be presented with various ad impressions that are intended to carry out promotional activities with the aim of making the goods sell well in the market. To prove this, the researchers carried out further research activities using quantitative research methods. Data collection is done by first distributing questionnaires to the informants. After the questionnaire data was collected, the data was then processed using SPSS software. The results of the study show that there is a positive and significant influence between Shopping Life Style and Advertising Media Stimulus on Customer Expectations (Case Study of Fashion Products). Keywords: Shopping Lifestyle and Advertising Media Stimulus, Customer Expectations